Tanzimat dönemi çağdaşlaşma çabaları - (:unkn) unknown (My University, 2011)
Bugüne kadar Tanzimat konusunda yazılmış pek çok husus olmasına rağmen, bu makalede amaç bir siyaset bilimcinin gözünden tarihçilerin kaynaklarını analiz ettikten sonra ortaya çıkan tabloyu okuyucunun dikkatine sunmaktır. Nitekim, bu çalışma Türkiye'de yaygın olarak iddia edilenin aksine, Cumhuriyet kurucularının bir Ortaçağ toplumuyla değil, son asrını modernleşme sancıları ve hayatta kalma mücadelesiyle geçiren İmparatorluğun bakiyesi bir toplumla yola çıktığı tarihsel gerçeğini bilimsel verilerle ortaya koymuştur. Bu bağlamda öncelikle Batı müesseselerinin Osmanlı Devleti'ne aktarılma sürecini oluşturan Tanzimat Dönemi'yle büyük bir ivme kazanan modernleşme evresi analiz edildi. Şark Meselesi eksenindeki uluslararası ortamda Osmanlı'nın hayatta kalma mücadelesi, Batının çeşitli kılıflardaki saldırıları, bir dönüm noktası teşkil eden 1856 Paris Barış Antlaşması ve Islahat Fermanı, Osmanlı maliyesinin çökmesi incelenerek günümüzdeki bazı olaylarla karşılaştırılması yapıldı. Ayrıca her ne kadar devlet yönetiminde çok fazla söz sahibi olmasa da Osmanlı aydınlarının zihniyet yapısının değişmesi ve ıslahatlara karşı yükselen muhalefet de ele alındı. Neticede ekonomik çöküşün ve yönetim bozulmasının önüne geçerek, toplumsal ilerlemeyi sağlayacak modernleşme hamlelerinin devamı olan bir yenileşme, batılılaşma girişimi olarak ortaya çıkan Tanzimat'ın, Avrupalıların maksatlı yönlendirmeleriyle İmparatorluğun dağılma sürecini nasıl hızlandırdığı da analiz edildi. Böylece bu durumu gören II. Abdülhamid'in iktidarı ele almasıyla farklı bir zemine kayacak olan Tanzimat süreci ana hatlarıyla incelenmiş oldu.

Although there are so far written several aspects of the Tanzimat, the aim of this article is to provide the resulting table after analyzing the so¬urces of historians, through the eyes of a political scientist. All of which are presented to the attention of the reader in this study. This article focu¬ses on the modernization process of Tanzimat in the Ottoman Turkey in which reconstructing of state and community accordance with the western standarts and values. In contrast to common claim in Turkey, the founders of the Republic did not face the medieval society, but faced the society that was in the throes of modernization and struggle for survival under the attacks of West and Russia within the axis of the Eastern Question. This study is revealed these historical and scientific facts. Thus we have to rethink the Ottoman Turkish modernizatin and discuss the how to Ottoman Empire modernized or westernized in the nineteenth century under the which conditions. Firstly, it is determined that there was no effects of west and supremacy of European civilization in the winds of change and it's felt in Ottoman depending on the initial reform movement. Ottoman perception of Europe in Tanzimat was dramatically changed. It is determined that in Tanzimat Term, the new western values have been sharply adopted and shaped under the military, political, administrative and executive targets. Later, Ottomans in the struggle for survival, several cases of West attacks within the context of the Eastern Question axis in the international environment was analysed. It is discussed that 1856 Paris Peace Treaty with Islahat Ferman which represents a turning point of West-Turkey relations, and the collapse of Ottoman finances are examined and comparision was made with some current events. In addition, the Ottomans's change of mentality social structure and the rising opposition of against reform movement in an overall assessment was also examined. To prevent the collapse of economic and administrative corruption, wish the social progress would provide a modernization, westernization initiative emerged as the Tanzimat, did not be succesfull due to purposeful direction of Europeans accelerate the process of disintegration of empi¬re. Opening of the modernization social-political, cultural and sociological to political interference which is multi-dimensional manifestations. In this modernization or westernization process would shift to different dimensi¬on when the Abdulhamit II take power.
Tanzimat Era modernization efforts
Keywords: Tarih; Siyasi Bilimler